Effects of Hot Packs on pain in patients with Osteoarthritis (OA) in Saidu Group of Teaching Hospital Swat: A Randomized Control Trial - Abdur Rahim, Shaier Khan, Samina Kausar, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The main objective of this study was to evaluate the effect of heat packs on pain in patients with osteoarthritis. Study design: A Randomized Control Trial Place and duration: Saidu Group of Teaching Hospital Swat for the period of six months. Methodology: Methods: This research employed a randomised controlled trial (RCT) design. A total of 60 patients met the inclusion criteria and were randomly assigned (30 in each) to either the experimental or control group. The severity of the pain was measured using a Visual Analog Scale. The patients in the control group received 20 minutes of heat therapy consisting of hot packs heated to 40 degrees Celsius administered to the affected joint. All patients were checked at day 0, day 3, day 8, and day 15 after treatment. Results: On days 8 and 15, patients in the experimental group reported significantly less pain than those in the control group (p = 0.002 and p 0.001, respectively). Patients younger than 50 years old in the study group experienced less pain on day 8th and 15th than those in the control group. Conclusion: As this study's findings indicate, using a hot pack can significantly reduce pain experienced by those suffering from osteoarthritis (OA). Further, it showed that the effectiveness of a hot pack on pain differed between patients based on factors including age and gender Keywords: Osteoarthritis, Hot pack, Randomized Control Trial, significant, convenient, cost effective.